Exposure to Parenting by Lying in Childhood: Associations with Negative Outcomes in Adulthood - Santos, Rachel M.; Zanette, Sarah; Kwok, Shiu M.; Heyman, Gail D.; Lee, Kang (Frontiers in Psychology, 2017)
Parents around the world engage in the practice of parenting by lying, which entails lying to manipulate children’s emotional states and behavior. The current study is the first to examine the potential associations between exposure to parenting by lying in childhood on later dishonesty and psychosocial maladjustment in adulthood. Female undergraduate adults retrospectively reported their experiences of parenting by lying during childhood, the current frequency at which they lie to their parents, and their current psychosocial functioning. We found that adults who recalled their parents using parenting by lying at relatively high levels during childhood both lie to their parents more often and experience greater psychosocial adjustment problems in adulthood compared to adults who recalled low levels of parenting by lying. This study is the first to suggest that parenting by lying during childhood may be associated with negative moral and social outcomes later in life.